Caracterização da dinâmica global de fusos do sono de pacientes com apneia obstrutiva através de sinais de eletroencefalografia - Reis, Tainá Pereira dos [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Sleep is a physiological state in which the subject has no apparent productive interaction with the environment. The electroencephalogram (EEG) is a widely used feature for the study of sleep and wakefulness. The structure of the EEG signal of sleep is related to the so-called microstructure of sleep, which is composed of graph elements such as the sleep spindles. In the present study the local spindle dynamics (LS) were characterized, which are observed by EEG channel and also by global spindles (GS), which occur simultaneously in all channels. Twenty-four patients with obstructive sleep apnea (OSA) were also divided into control groups with mild and moderate OSA in the Neurology sector of the Hospital de Clínicas of Porto Alegre between 2007 and 2009. An automatic detection method based on the Matching Pursuit technique. The spindles were located and determined when they occurred, after which an exponential and q-exponential adjustment of the temporal distribution of the intervals of the difference between two consecutive spindles was performed. By comparing the adjustments, evaluated by the Bayesian quality criterion (BIC), it was verified that the temporal distribution of LS of the analyzed individuals is better adjusted by the q-exponential function, whereas the GS distribution is best described by an exponential law . The analyzed parameters presented significant differences only in the f3 channels of the LS and in the relation between the control patients and moderate AOS of the SG. The behavior of the amplitude as a function of the time of occurrence of the spindles was also analyzed and the groups of spindles found were denominated of communities or clusters. From this, a clustering method implemented in Python was used to obtain the duration of the communities and number of LS and GS in them. The estimates of spindle densities, obtained by linear adjustment of the relationship between the duration of the clusters and the number of spindles present in them, were significant only in the study of the global spindles. The methodology developed was also applied to evaluate the distribution of the duration of the spindle communities of each EEG examination and it was verified that it obeys a power law. In this way, our results demonstrate that it is possible to characterize the spindle dynamics through the EEG examination and that the global spindles are better suited for the study of the physiological alterations caused by Obstructive Sleep Apnea

O sono é um estado fisiológico em que o indivíduo não apresenta interação produtiva aparente com o ambiente. O eletroencefalograma (EEG) é um recurso amplamente utilizado para o estudo de sono e vigília. A estrutura do sinal de EEG do sono está relacionada com a chamada microestrutura do sono, que é composta por grafoelementos, como os fusos do sono. No presente estudo foi caracterizada a dinâmica de fusos locais (FL), os quais são observados em cada canal de EEG e também de fusos globais (FG), que ocorrem simultaneamente em todos os canais. Para isto, vinte e quatro pacientes portadores de Apneia Obstrutiva do Sono (AOS) foram divididos, igualmente, em grupos controle, com AOS leve e moderada no setor Neurologia do Hospital de Clínicas de Porto Alegre entre os anos 2007 e 2009. Foi aplicado um método automático de detecção baseado na técnica do Matching Pursuit. Os fusos foram localizados e foi determinado quando ocorreram, posteriormente foi realizado um ajuste exponencial e q-exponencial da distribuição temporal dos intervalos da diferença entre dois fusos consecutivos. Através da comparação entre os ajustes, avaliados pelo critério de qualidade Bayesiano (BIC), foi verificado que a distribuição temporal de FL dos indivíduos analisados é melhor ajustada pela função q-exponencial, enquanto que a distribuição de FG é melhor descrita por uma lei exponencial. Os parâmetros analisados apresentaram diferenças significativas apenas nos canais f3 dos FL e na relação entre os pacientes controle e AOS moderada dos FG. O comportamento da amplitude em função do tempo de ocorrência dos fusos também foi analisado e os agrupados de fusos encontrados foram denominados de comunidades ou clusters. A partir disto, foi utilizado um método de clusterização implementado em Python para obtenção da duração das comunidades e número de FL e FG existentes nelas. As estimativas das densidades de fusos, obtidas através do ajuste linear da relação entre a duração dos clusters e o número de fusos presentes neles, foram significativas apenas no estudo dos fusos globais. A metodologia desenvolvida também foi aplicada para avaliar a distribuição da duração das comunidades de fusos de cada exame de EEG e foi constatado que esta obedece uma lei de potência. Desta maneira, os nossos resultados monstram que é possível caracterizar a dinâmica dos fusos através do exame de EEG e que os fusos globais são mais indicados para o estudo das alterações fisiológicas causadas pela Apneia Obstrutiva do Sono
Keywords: Electroencephalogram; Sleep; Sleep spindles; Obstructive sleep apnea; Temporal distribution and communities.; Eletroencefalograma; Sono; Fusos do sono; Apneia obstrutiva do sono; Distribuição temporal e comunidades